Atomic-scale investigation of the interface precipitation in a TiB2 nanoparticles reinforced Al–Zn–Mg–Cu matrix composite. (15th February 2020) - Ma, Yu; Addad, Ahmed; Ji, Gang; Zhang, Ming-Xing; Lefebvre, Williams; Chen, Zhe; Ji, Vincent
Abstract: The effects of nanosized reinforcement particles on precipitation reactions in age-hardenable Al alloy matrix composites have been largely unknown. In this work, an Al–Zn–Mg–Cu matrix composite reinforced with uniformly distributed TiB2 nanoparticles was successfully produced. The solid-soluted, peak-aged and overaged materials were then characterized, at the atomic scale using (high-resolution) scanning transmission electron microscopy, to provide a fundamental insight into the interface precipitation. Our results demonstrated that the facetted TiB2 nanoparticles have a significant impact on the precipitation in matrix areas adjacent to the TiB2 /Al interfaces. The interfaces after solid-solution treatment are tightly-bonded and oxide-free. The TiB2 particles and Al matrix display two orientation relationships (ORs): the well-reported [2 1 ¯ 1 ¯ 0]TiB2 //[101]Al, (0001)TiB2 //( 1 ¯ 11)Al (OR1) and the new [2 1 ¯ 1 ¯ 0]TiB2 //[101]Al, (01 1 ¯ 0)TiB2 //(11 1 ¯ )Al (OR2). The interface precipitates (i.e., interphase) having the size of several tens of nanometers were formed after ageing and were determined to be (Zn1.5 Cu0.5 )Mg phase. Their formations were only related to the initial OR1 and OR2 where the mutual ORs between the TiB2, interphase and Al matrix were further developed. Periodically spaced misfit dislocations were revealed at the semi-coherent TiB2 /Al interfaces, which are generally considered beneficial to the heterogeneous precipitation. They not only reduced nucleation energy barrier, but also acted as short-circuit diffusion paths for transporting solute atoms and vacancies, accelerating growth rate. However, the growth of interphase at the interface parallel to close-packed {111} Al planes was suppressed by the ultra-low accommodation factor. In addition, such an interface precipitation reduced the mismatch of the TiB2 /Al interface, increasing the overall coherency and being potential for effective interface strengthening. Graphical abstract: Image, graphical abstract